Chemical Castration Execution Model Through The Administration of Police Medical Operation - Kodrat Alam (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Prosecutors as executors of court decisions are required to be able to be anticipatory in the process of law enforcement against sexual violence crimes following medical doctors’ refusal to be involved in the execution of chemical castration. This study aims to find a model of chemical castration execution that can be applied through the administration of police medical operation (Dokpol) which combines the roles and positions of medical doctors and law enforcers simultaneously to support the implementation of police duties. The statements of the problem are set to find answers to the questions: Should the execution of chemical castration imposed by the court always be carried out? And can chemical castration be carried out through the implementation of police duties? The research method used is a normative juridical method. The availability of resources of police medical operation who have competence in the health sector is expected to be a solution for prosecutors to prepare chemical castration executors in accordance with the provisions required in Article 9 letter b of Government Regulation No. 70 of 2020, in order to achieve legal certainty regarding the implementation of the Mojokerto District Court decision whose execution is planned to take place in 2031.